2021
DOI: 10.1002/adom.202001947
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Near‐Infrared Laser Dyes through a Shift in Excited‐State Absorption

Abstract: The development of near‐infrared (NIR) light sources has attracted much interest due to their attractive applications, such as biosensing and light detection and ranging (LiDAR). In particular, organic semiconductor laser diodes with NIR emission are emerging as a next generation technology. However, organic NIR emitters have generally suffered from a low quantum yield, which has resulted in only a few examples of organic solid‐state NIR lasers. In this study, the authors demonstrate a highly efficient NIR emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…The existence of re‐absorption, singlet‐singlet excited state absorption, charge absorption, and triplet‐triplet excited state absorption is known to affect the light amplification properties. [ 2,18,19 ] Therefore, the effective σ em (λ) (σ em, eff (λ)) is defined by the following equation (Equation ()): [ 59,60 ] σem, eff λ=σem λσabsλσSSλσchargeλσTTλ where σ abs (λ) is the absorption cross‐section of the ground‐state species, σ S‐S (λ) is absorption cross‐section of the singlet‐singlet excited‐state species, σ charge (λ) is charge absorption cross‐section, and σ T‐T (λ) is triplet‐triplet excited‐state absorption cross‐section. Due to the negligible overlap between host PIA and effective gain regions from TA measurements, σ S‐S (λ), σ charge (λ) and σ T‐T (λ) at each selected emission wavelength are almost zero in the BEHP‐PPV:MEH‐PPV blend system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of re‐absorption, singlet‐singlet excited state absorption, charge absorption, and triplet‐triplet excited state absorption is known to affect the light amplification properties. [ 2,18,19 ] Therefore, the effective σ em (λ) (σ em, eff (λ)) is defined by the following equation (Equation ()): [ 59,60 ] σem, eff λ=σem λσabsλσSSλσchargeλσTTλ where σ abs (λ) is the absorption cross‐section of the ground‐state species, σ S‐S (λ) is absorption cross‐section of the singlet‐singlet excited‐state species, σ charge (λ) is charge absorption cross‐section, and σ T‐T (λ) is triplet‐triplet excited‐state absorption cross‐section. Due to the negligible overlap between host PIA and effective gain regions from TA measurements, σ S‐S (λ), σ charge (λ) and σ T‐T (λ) at each selected emission wavelength are almost zero in the BEHP‐PPV:MEH‐PPV blend system.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of re-absorption, singlet-singlet excited state absorption, charge absorption, and triplet-triplet excited state absorption is known to affect the light amplification properties. [2,18,19] Therefore, the effective σ em (λ) (σ em, eff (λ)) is defined by the following equation (Equation ( 6)): [59,60] em, eff em abs SS c harge TT…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…We combined two DHMAC molecules to elongate the π-conjugation length, which leads to a narrowing of the highest occupied molecular orbital-lowest unoccupied molecular orbital (HOMO-LUMO) energy gap and results in further red shift emission (Fig. 1b, c) [54,55]. A larger π-conjugated system can strengthen the intermolecular π-π interaction, which is helpful for the formation of uniaxially oriented molecular crystals [56].…”
Section: Resultsmentioning
confidence: 99%
“…Within the examples reported here, we showed that the polymethine character can be correlated to some extend to the presence and the broadening of ENZ spectral region in pristine thin lm. The dyes with CT character work efficiently for emissive organic electronics applications 21,23,24 while not showing ENZ properties. On the other hand, the polymethine character in Curc dyes is associated with characteristics related to ENZ materials.…”
Section: Discussionmentioning
confidence: 99%